Characterization of Lavandula multifida volatile composition from Morocco by headspace solid-phase Microextraction (HS-SPME) and Hydrodistillation coupled to GC–MS - Znini M; Laghchimia A; Paolinib J; Costab J; Majidia L (Arabian Journal of Medicinal and Aromatic Plants, 2019)
The essential oil and volatiles compounds of Lavandula multifida L., aerial parts collected in South-East Morocco, obtained by hydrodistillation (HD) and headspace solid phase Microextraction (HS-SPME), were analyzed using Gas Chromatography-Flame Ionization Detector (GC-FID) and GC-Mass Spectrometry (GC-MS). 31 components, accounting 94.3% in the total essential oil, were identified by HD and 21 compounds, representing 90.2% of the headspace, were characterized by HS-SPME. The major components identified are carvacrol (57.9% ; 65.6%), carvacrol methyl ether (7.6% ; 4.6%), p-cymen-8-ol (3.9% ; 4.8%) and spathulenol (3.8% ; 8.6%) of essential oil and volatile compounds detected in HS-SPME, respectively. By comparison of HD and HS-SPME extraction, only quantitative diﬀerences of some components can be observed in both aromatic proﬁles, while qualitatively are rather similar. This study demonstrates that HD and HS-SPME modes could be complimentary extraction techniques in order to obtain the complete characterization of plant volatiles.